Further electrical and electronic principles - Robertson, Christopher R. (Elsevier/Newnes, 2008)
Further Electrical and Electronic Principles is a core text for pre-degree courses in electrical and electronic engineering courses. The coverage of this new edition has been brought in line with the specialist unit 'Further Electrical Principles' of the 2007 BTEC National Engineering specification from Edexcel. As the book follows a logical topic progression rather than a particular syllabus, it is also suitable for other Level 3 students on vocational courses such as Vocational AS/A Level, City & Guilds courses and NVQs. More advanced material has also been included, making this text also sui.